Potret Kehidupan Wanita Ke Dunia Prostitusi Pasca Perceraian di Kabupaten Merauke: A Portrait of Women's Life in Prostitution after Divorce in Merauke Regency - Sriyono, Damario; Faisal, Faisal; Yamin, Ade (Institut Agama Islam Negeri Fattahul Muluk Papua, 2025)
The high rate of prostitution in Merauke Regency is a concern because it causes social problems, this phenomenon is not a single phenomenon because there is another phenomenon, namely the high divorce rate in Merauke Regency. This study aims to determine the relationship between female sex workers (FSWs) in prostitution and divorce. Then this research will also look at the factors that cause a FSW to work in a prostitution place. The research method used in this research is a descriptive qualitative research method approach, namely this research aims to determine the relationship between the number of workers in prostitution and divorce that occurs in Merauke Regency, so that the results of the research can be used as a reference for policy makers to control prostitution practices that occur in society. The results showed that this study found that the workers in the prostitution place were the majority of women who were widowed approximately 51%. This proves that as a result of divorce or separation from her husband, these wives or women choose to work in prostitution to fulfil the lives of her and her family. The next research finding is the dominant factor that causes FSWs to work in prostitution because of economic factors that make these women have to work improperly.